Computational Simulation for the Fragmentation Regimes by Using Droplet Breakup Model (Journal of University of Babylon for Engineering Sciences, 2018)
There are no numerical research paper attempts to simulate the break-up mechanism of droplets in the spray development.  In particular, the work described here refers to study and quantify the break-up of droplets regime and their effects on the spray behavior. With this purpose, the model parameters results, based on droplet break-up model proposed by Reitz and Diwakar [1] and momentum flux calculations are performed. The parameters that are used in the droplet break-up model are stored in the code as properties. These properties are saved in every computation cell. The parameters are Weber number, break-up time and stable droplet diameter. The numerical simulation is implemented as Eulerian-Eulerian approach. The spray moments theory is used for the liquid phase. Finally the study is implemented in a conceptual model to investigate the possible benefits of the droplet break-up model. A good agreement for the numerical results are compared with the experimental data for the spray tip penetration.